Multiple E-Region Radar Propagation Modes Measured by the VHF SIMONe Norway System During Active Ionospheric Conditions - Huyghebaert, Devin; Clahsen, Matthias; Chau, Jorge L.; Renkwitz, Toralf; Latteck, Ralph; Johnsen, Magnar G.; Vierinen, Juha (Frontiers in Astronomy and Space Sciences, 2022)
Multiple propagation modes between different bistatic radar links were measured during the operations of a very high frequency (VHF) 32.55 MHz radar system in northern Norway. The Spread Spectrum Interferometric Multistatic meteor radar Observing Network (SIMONe) Norway system detected meteor trails, direct transmitter to receiver signal propagation, over-the-horizon signal propagation from the SIMONe Germany system, ground and/or sea scatter, and ionospheric scatter on 27 August 2021 between 16:30–20:00 UT. These simultaneous detections were during an active ionospheric period with multiple occurrences of energetic charged particle precipitation. The SIMONe systems used continuous-wave (CW) pseudo-random phase modulated transmit signals and interferometry to make it possible to isolate each of these propagation modes and examine their characteristics. Different multistatic links at three receiver locations were analyzed, providing multistatic measurements of the regions with spatial and temporal resolutions on the order of 1.5 km and 2 s. The analysis techniques are described, with characteristics of the radar signal presented for each propagation mode and multistatic link. This study serves to highlight the capabilities of the SIMONe Norway system to research multiple aspects of ionospheric phenomena, specifically in the lower thermosphere-mesosphere boundary region.